Evaluation of the HR Management and Organization Capacity of Bapenda for Optimizing Regional Fiscal Independence - Tino Rahmat Riyadi; Nanda Ayu Wijayanti (Green Publisher Indonesia, 2024)
This research aims to evaluate the capacity of the Tegal Regency Regional Revenue Agency as a regional tax management organisation based on the two OECD pillars, namely human resource management, and organisational management, to assist the Tegal district government's efforts to increase fiscal independence. This research uses a qualitative approach with a case study method. Primary data sources are interviews with seven respondents at the Regional Revenue Management Agency of Tegal Regency and secondary data in the form of documents related to the research topic. The results of the research show that the condition of human resource management capacity and organisational management of the Tegal Regency Bapenda still requires further capacity development, especially capacity in the medium and significant categories. Some of the problems that still need further capacity development include those related to the competence of employees at Bapenda who do not fully fulfil tax administration functions, the division of tasks and authority that is still not effective. Also, there are still policies that have not been evaluated and updated regularly. This research is expected to provide an overview of the condition of human resource management capacity and the Tegal Regency Bapenda organisation's management of regional taxes so that it can be used as a reference in planning organisational capacity development in an effort to achieve regional fiscal independence.